Központi funkciók feltárása Vas megyében - Lenner, Tibor (Tér és Társadalom, 1996)
The development of urbanisation in Vas county was influenced by both local and national processes. Following World War II, the county found itself in an unfavourable situation because of its location along the western border, thus its peripheral situation further worsened. Significant industrial investments neglected this county, its traditional trading connections vanished, consequently its population decreased, outmigration started and the development of the towns stagnated, too. The analysed data reveal that fact that the small towns as the attraction centres in Vas county could only meet the criteria of the central role with contradictions. We can practically say that there is a direct proportion in the chronology of the towns obtaining this status and their places in the urban hierarchy, i.e. the younger they are the lower they can be found in the hierarchy. It is absolutely the case with Vasvár and Csepreg, their functions are still rather deficient.